Evaluación de los emprendimientos en la satisfacción de la demanda turística costa norte de Manabí post terremoto - Ureta Villavicencio, Henry Adrian (2021)
The objective of this work was to evaluate the satisfaction of the tourist demand of the enterprises of the north coast of Manabí after the earthquake, specifically in the cantons Jama and Pedernales. This is a qualitative research with a descriptive exploratory approach. The methodological design is comprised of 3 phases. First, it was based on the characterization of the study area, an observation file and field trips were used to analyze the territory and its undertakings, then a bibliographic review of official documents, cadastres and tourist inventories was carried out, to finish an analysis was carried out. strategic using a SWOT matrix. In the second phase, the undertakings are evaluated, a registration form was made using the official cadastre, then they were analyzed considering quality indicators from MINTUR (2016). To conclude, the HOTELQUAL matrix is used, which evaluated the perception of the demand, 196 questionnaires were applied to the clients. Similarity was observed in natural and cultural resources, while in plant and tourist facilities Pedernales is more developed. For this work, 4 hotels are considered in Jama and in Pedernales 9. Where it was determined that the Hotel Bocana de Quiximies is one of the establishments that provided the greatest satisfaction to tourists, with a score of 4.77 / 5, which has comfortable facilities and adequate staff to provide a quality service. 6 strategies and 19 actions were proposed trying to solve aspects that do not allow tourism to develop with quality in the north of Manabí.